New utilizations of natural CuFeS2 as the raw material of Cu smelting for recovering Hg0 from Cu smelting flue gas. (1st June 2023) - Ding, Zhen; Yang, Chen; Zhang, Huan; Mei, Jian; Wang, Jian; Yang, Shijian
Graphical abstract: Highlights: Acid-treated CuFeS2 is derived from the simple acid treatment of natural CuFeS2. Acid-treated CuFeS2 displays a superior performance in capturing Hg 0 . The spent acid-treated CuFeS2 can be reused for Cu smelting. Most Hg 0 in the Cu-SFG can be recovered as liquid Hg by acid-treated CuFeS2 . Abstract: Limits on Hg 0 emissions from Cu smelting flue gas (Cu-SFG) are stipulated severely by the Minamata Convention. In this work, acid-treated CuFeS2, derived from the simple acid treatment of natural CuFeS2 as the raw material of Cu smelting, was developed as a reusable sorbent to recover Hg 0 in the Cu-SFG. Hg 0 capture by natural CuFeS2 was closely related to the amounts of adsorption sites and active S2 2− . After acid treatment, not only the surface of natural CuFeS2 became porous and roughened, but also some impurities in it were removed; hence, more adsorption sites for Hg 0 adsorption and more active S2 2− for oxidizing Hg 0 adsorbed were formed on acid-treated CuFeS2, causing its superior performance in capturing Hg 0 . Moreover, after acid treatment and Hg 0 capture, the property of natural CuFeS2 for Cu smelting barely varied, implying that the spent acid-treated CuFeS2 may be reused. Furthermore, most Hg 0 in the Cu-SFG can be recovered as liquid Hg using the condensers in Cu smelters. Therefore, Hg 0 recovery using acid-treated CuFeS2 was an economically viable and eco-friendly method to control Hg 0 emissions from the Cu-SFG, double as a viable way to develop the new utilization of natural CuFeS2 as the raw material of Cu smelting.